Effects of COVID-19 pandemic lockdowns on college students’ physical fitness: A comparative study - Jianzhong Sun; Minghao Wu; Jun Li; Cunjian Bi (PLoS ONE, 2025)
Background The impact of the COVID-19 outbreak has been significant and far-reaching. This paper retrospectively examines its effects on changes in the physical fitness of university students. Method From 2018 to 2020, a comprehensive undergraduate institution in southern Anhui Province was selected to assess the impact of the COVID-19 pandemic on physical health indicators among college students. Results The overall physical fitness of students at Chizhou University was clustered near the passing threshold of 80.8%, with 13.0% of students failing to meet the standard. The COVID-19 pandemic contributed to an increased prevalence of overweight (11.3%) and obesity (4.4%) among the student population. In endurance running, both male and female students displayed a similar trend—initial improvement followed by a decline—resulting in reduced performance times by 16.7 s for males and 13.2 s for females in 2020. Notably, vital capacity and upper limb strength showed consistent upward trends from 2018 to 2020 for both genders. Specifically, male students’ vital capacity increased by 2.0% and 3.4%, and upper limb strength by 4.8% and 8.3%, in consecutive years. Similarly, female students’ vital capacity rose by 1.3% and 4.4%, while their upper limb strength improved by 3.9% and 3.5%, respectively. Conclusion The short-term impact of the COVID-19 epidemic significant effected college students’ endurance running performance. Future efforts should focus on the important long-term lagging effects of the pandemic. Meanwhile, there is an urgent need to better understand and develop alternative exercise modalities during major public health events to ensure the maintenance of physical fitness and overall health.